Pudaman Initiative: Revolutionizing School Health Reporting with Technology - Kusumaratna, Rina K; Alifia, Khansa; Putri, Chika Oktadiana (Universitas Nusantara PGRI Kediri, 2026)
Dengue is the most prevalent and rapidly spreading vector-borne disease globally. In Indonesia, the Mosquito Nest Eradication (PSN) program is a key component of the School Health Effort (UKS), aimed at preventing Dengue Hemorrhagic Fever (DHF) in educational settings. However, the implementation of school-based mosquito cadres (PUDAMAN) remains limited at the junior and senior high school levels. Jakarta Provincial data reported a rise in dengue cases in South Jakarta between January and March 2024, with Pondok Labu sub-district recording nine cases and an incidence rate of 31.12. In response, the sub-district UKS coordinator conducted health promotion activities involving 85 students and teachers from eight junior high schools (March–April 2024). The intervention included dengue-related education, technology-based reporting, and hands-on training in advocacy, collaboration, and prevention. Evaluation using the Wilcoxon signed-rank test showed a statistically significant 50% increase in participant understanding (p = 0.000). These findings demonstrate that participatory health promotion strategies when integrated into school settings through digital tools and community engagement can effectively empower students in vector surveillance and strengthen early detection and prevention efforts in dengue-endemic areas.